Hominoid-specific enzyme GLUD2 promotes growth of IDH1R132H glioma - Chen, Ruihuan; Nishimura, Merry C; Kharbanda, Samir; Peale, Frank; Deng, Yuzhong; Daemen, Anneleen; Forrest, William F; Kwong, Mandy; Hedehus, Maj; Hatzivassiliou, Georgia; Friedman, Lori S; Phillips, Heidi S (Proceedings of the National Academy of Sciences - PNAS, 2014)
Somatic mutation of isocitrate dehydrogenase 1 (IDH1) is now recognized as the most common initiating event for secondary glioblastoma, a brain tumor type arising with high frequency in the frontal lobe. A puzzling feature of IDH1 mutation is the selective manifestation of glioma as the only neoplasm frequently associated with early postzygotic occurrence of this genomic alteration. We report here that IDH1(R132H) exhibits a growth-inhibitory effect that is abrogated in the presence of glutamate dehydrogenase 2 (GLUD2), a hominoid-specific enzyme purportedly optimized to facilitate glutamate turnover in human forebrain. Using murine glioma progenitor cells, we demonstrate that IDH1(R132H) exerts a growth-inhibitory effect that is paralleled by deficiency in metabolic flux from glucose and glutamine to lipids. Examining human gliomas, we find that glutamate dehydrogenase 1 (GLUD1) and GLUD2 are overexpressed in IDH1-mutant tumors and that orthotopic growth of an IDH1-mutant glioma line is inhibited by knockdown of GLUD1/2. Strikingly, introduction of GLUD2 into murine glioma progenitor cells reverses deleterious effects of IDH1 mutation on metabolic flux and tumor growth. Further, we report that glutamate, a substrate of GLUD2 and a neurotransmitter abundant in mammalian neocortex, can support growth of glioma progenitor cells irrespective of IDH1 mutation status. These findings suggest that specialization of human neocortex for high glutamate neurotransmitter flux creates a metabolic niche conducive to growth of IDH1 mutant tumors.